Kendala Transit Time Performance Pada Proses Pengiriman Barang - Ashari Syafril; Tiara Herzenia Putri; Subandi Subandi (Institut Transportasi dan Logistik Trisakti, 2021)
This study aims to determine the constraints on the Transit Time Performance at the DHL Express Service Center Karawaci. The data used are primary data and secondary data. The samples studied were 27 respondents. In this study, using 17 types of main categories (types of causative factors). The results of the factor analysis test show that of the 17 types of main categories that survive in the model and group them into 5 factors, the factors that affect the constraints on Transit Time Performance. These factors are the number of employees with a percentage of 40%, the work hours factor of employees with a percentage of 30%, the scanner performance factor with a percentage of 20% and the bonus factor with a percentage of 10%. The dominating factor is the number of employees which has a percentage of 40%. The factors that are formed are then analyzed using the Fishbone Diagram method to determine the causative factors graphically, so that the company can take preventive and corrective actions to reduce the error rate in service quality.